Cysteinyl-tRNA synthetase is not essential for viability of the archaeon Methanococcus maripaludis - Stathopoulos, Constantinos (The National Academy of Sciences, 2001)
The methanogenic archaea Methanocaldococcus jannaschii and Methanothermobacter thermautotrophicus contain a dual-specificity prolyl-tRNA synthetase (ProCysRS) that accurately forms both prolyl-tRNA (Pro-tRNA) and cysteinyl-tRNA (Cys-tRNA) suitable for in vivo translation. This intriguing enzyme may even perform its dual role in organisms that possess a canonical single-specificity cysteinyl-tRNA synthetase (CysRS), raising the question as to whether this latter aminoacyl-tRNA synthetase is indeed required for cell viability. To test the postulate that all synthetase genes are essential, we disrupted the cysS gene (encoding CysRS) of Methanococcus maripaludis. The knockout strain was viable under normal growth conditions. Biochemical analysis showed that the pure M. maripaludis ProCysRS was capable of forming Cys-tRNA, implying that the dual-specificity enzyme compensates in vivo for the loss of CysRS. The canonical CysRS has a higher affinity for cysteine than ProCysRS, a reason why M. maripaludis may have acquired cysS by a late lateral gene transfer. These data challenge the notion that all twenty aminoacyl-tRNA synthetases are essential for the viability of a cell.